Silicon carbide bipolar junction transistor with novel emitter field plate design for high current gain and reliability. (28th February 2019) - Zhang, Yourun; Chen, Hang; Luo, Maojiu; Li, Juntao; Wang, Wen; Deng, Xiaochuan; Bai, Yun; Chen, Hong; Zhang, Bo
Abstract: A silicon carbide bipolar junction transistor with novel emitter field plate (EFP-BJT) design is proposed in this paper. The fabricated EFP-BJT features a metal plate of the extending emitter electrode with a 50-nanometer-thick oxide layer overlapped on the extrinsic base surface. The contrast of experimental results show that a 56% increase of maximum current gain is obtained by the EFP-BJT compared with a conventional SiC BJT (C-BJT), with the EFP-BJT's current gain of 43 measured at the collector current density ( J C ) of 716 A cm −2 corresponding to a specific on-state resistance ( R SP_ON ) of 5.4 mΩ · cm 2 and open-base breakdown voltage ( BV CEO ) of 1.5 kV. The novel EFP-BJTs are entirely compatible with the process and design considerations of the conventional ones. The in-depth mechanism comparisons between the proposed EFP-BJT and C-BJT are studied by the simulation tool TCAD Silvaco. The surface recombination effect of EFP-BJT is greatly reduced by the modulation of the emitter field plate. Additionally, due to the surface recombination suppression of the novel structure, EFP-BJTs have effectively enhanced reliability. Compared with C-BJTs, there is no significant degradation of the collector current for the fabricated EFP-BJTs under the forward current stress test.